ANALISIS FAKTOR YANG MEMPENGARUHI NIAT PEMBELIAN KEMBALI PRODUK MEWAH MEREK LOUIS VUITTON DI JAKARTA - Rizka Rahma Kusumadewi (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
The development of the fashion industry becomes very important in various circles both among the young and the aged. This industry has grown rapidly, both women and men’s fashion. The rapid advancement of information technology and is also one of the causes of fashion has penetrated into all levels of society, including in Indonesia. Already a lot of people who want to look nice and different from other people in the surrounding areas, especially in the association, appearance is important to note, even the appearance usually be supported with branded products are also exclusive. This research aims to analyze the effect of hedonism, materialism, social status, conspicuous value, uniqueness value, price perception, quality of product on the intention to repurchase luxury product brand Louis Vuitton (LV) in Jakarta. This research was conducted using a quantitative approach with a survey method and the data was collected using questionnaire which were distributed to 250 respondents in Jakarta. The data analysis methods used in this study are multiple linear regressions, the classical assumptions test, and hypothesis testing. The results showed that all the hypotheses were supported. The conclusions of this research are, the hedonism, materialism, social status, conspicuous value, uniqueness value, perception of price, quality of product has a positive effect on the intention to repurchase luxury product brand Louis Vuitton (LV).